2018
DOI: 10.1039/c8ra05430d
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a dynamic intestinal gut-on-a-chip barrier model for transport studies of lipophilic dioxin congeners

Abstract: Novel microfluidic technologies allow the manufacture of in vitro organ-on-a-chip systems that hold great promise to adequately recapitulate the biophysical and functional complexity of organs found in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 71 publications
1
39
0
1
Order By: Relevance
“…No other studies on the effects of shear www.nature.com/scientificreports/ www.nature.com/scientificreports/ forces on Caco-2 cells based on transcriptomics data could be found. As reported previously, cells grown under dynamic conditions seemed to be larger compared to cells grown under static conditions 12,13 . The morphology of Caco-2 cells has been shown to be affected by differences in shear forces.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…No other studies on the effects of shear www.nature.com/scientificreports/ www.nature.com/scientificreports/ forces on Caco-2 cells based on transcriptomics data could be found. As reported previously, cells grown under dynamic conditions seemed to be larger compared to cells grown under static conditions 12,13 . The morphology of Caco-2 cells has been shown to be affected by differences in shear forces.…”
Section: Discussionsupporting
confidence: 84%
“…Design of the gut-on-chip system. The microfluidic gut-on-chip device has been developed and described previously 12,13 . Briefly, the chip consists of three 15 × 45 mm (width x length) re-sealable glass slides that result in two flow chambers (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first-generation microscale cell culture analog (μCCA) devices mimicking the organ-level function of human physiology were fabricated on silicon ( Sin et al, 2004 ; Mahler et al, 2009 ). Compared to opaque silicon, glass is optically transparent and optimal for real-time imaging, while reducing the absorbance of hydrophobic molecules and the adsorption of biomolecules ( Lee S. et al, 2017 ; Kulthong et al, 2018 ). Nevertheless, glass chips with enclosed channels are not suitable for long-term cell culture because glass is not gas permeable.…”
Section: Materials For Oocsmentioning
confidence: 99%
“…As shown in Table 1, the apparent permeability coefficients observed in our study corresponds with the range of data found in the literature. Comparison of our dynamic automated system with other dynamic systems is challenging as there is a high variety in designs and there are only a limited number of studies examining the absorptive capacity of the model [10,14,20,40,41]. For a widespread use of dynamic in vitro intestinal barrier models and incorporation of them in drug development trials and risk assessment approaches, more permeability data of model compounds needs to be generated using the dynamic devices, including benchmarking against the static Transwell and in vivo data.…”
Section: Temporal Analysis Of Intestinal Permeabilitymentioning
confidence: 99%